Functional capacity and quality of life of patients with chronic wounds (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To evaluate functional capacity and quality of life (QoL) of patients with chronic wounds. Methods: A cross-sectional analytical study composed of 74 patients with chronic wounds accompanied at a reference center for the treatment of complex wounds in Teresina, state of Piaui. Data were collected using the Katz index and the Cardiff Wound Impact Schedule. Results: Among the domains, the “well-being” had a lower mean score and the degree of dependence obtained a signifi cant association with the well-being and “social life” domains. The bathing, dressing, personal hygiene and locomotion activities showed an association between the domains of QoL. Conclusion: The degree of independence in performing the basic activities of daily living, especially bathing, dressing and personal hygiene, presented higher scores between domains, indicating a better QoL. It is expected that the implantation of measures that help to preserve the functional capacity will improve the patients’ QoL.
Keywords: Wounds and injuries; Quality of life; Daily activities; Stomatherapy